MHD and rotation effects on flow past an accelerated vertical plate with variable temperature and mass diffusion in the presence of chemical reaction - Muthucumaraswamy, Rajamanickam; Dhanasekar, Nagarajan; Easwara Prasad, G. (Zielona Góra: Uniwersytet Zielonogórski)
An exact analysis of rotation effects on an unsteady flow of an incompressible and electrically conducting fluid past a uniformly accelerated infinite isothermal vertical plate, under the action of a transversely applied magnetic field is presented. The plate temperature is raised linearly with time and the concentration level near the plate is also raised to C?w. The dimensionless governing equations are solved using the Laplace-transform technique.
Keywords: rotation; accelerated; isothermal; vertical plate; heat transfer; diffusion; magnetic field; chemical reaction